Mode Switching and Filtering in Nanowire Lasers - Roeder,R; Sidiropoulos,TPH; Buschlinger,R; Riediger,M; Peschel,U; Oulton,RF; Ronning,C (Nano Letters, 2016)
Coherent light sources confining the light below the vacuum wavelength barrier will drive future concepts of nanosensing, nanospectroscopy, and photonic circuits. Here, we directly image the angular emission of such a light source based on single semiconductor nanowire lasers. It is confirmed that the lasing switches from the fundamental mode in a thin ZnO nanowire to an admixture of several transverse modes in thicker nanowires approximately at the multimode cutoff. The mode competition with higher order modes substantially slows down the laser dynamics. We show that efficient photonic mode filtering in tapered nanowires selects the desired fundamental mode for lasing with improved performance including power, efficiency, and directionality important for an optimal coupling between adjacent nanophotonic waveguides.